Quality of life among post-menopausal women due to oxidative stress boosted by dysthymia and anxiety - Sánchez-Rodríguez, Martha A. (BMC Womens Health, 2017)
BACKGROUND: Menopause is the onset of aging in women. During this process, some women experience physical changes that may impact upon their psychological and social status, also affecting their quality of life. Furthermore, several psychological changes following menopause have been shown to act as pro-oxidant, but the association between the psychological status that modify the quality of life and oxidative stress in postmenopausal women is still unclear. The aim of this study was to determinate the relationship between oxidative stress with psychological disturbances, low self-esteem, depressive mood and anxiety, and quality of life in the postmenopausal women. METHODS: We carried out a cross-sectional study with101 premenopausal and 101 postmenopausal women from Mexico City. As markers of oxidative stress we measured plasma lipoperoxide levels, erythrocyte superoxide dismutase and glutathione peroxidase activities, and total antioxidant status. We calculate a stress score as global oxidative stress status, with cut-off values for each parameter; this score range from 0 to 6, representing the severity of markers modifications. All the women were rated using the Coopersmith Self-Esteem Inventory, the Zung Self-Rating Anxiety and the Zung Self-Rating Depression Scales, and the WHO Quality of Life-brief. RESULTS: The postmenopausal women with low quality of life in the WHO Quality of Life-brief and their subscales had higher stress score compared with premenopausal women with high quality of life (p < 0.05). We found a positive correlation among lipoperoxide levels and Zung Self-Rating Anxiety and Zung Self-Rating Depression score (r = 0.226 and r = 0.173, respectively, p < 0.05), and a negative correlation with WHO Quality of Life-brief scores (r = −0.266, p < 0.01) in postmenopausal women. Multiple linear regression analysis revealed that average lipoperoxide levels increase by 0.0007 μmol/L for every 1-point increase in the Coopersmith Self-Esteem Inventory and by 0.001 μmol/L for every 1-point decrease in the WHO Quality of Life-brief, after adjusted for pro-oxidant factors. Zung Self-Rating Anxiety and Zung Self-Rating Depression Scales scores also contribute to increase lipoperoxides levels, but not significant. CONCLUSION: Our findings suggest that oxidative stress is increased in postmenopausal women with psychological disturbances and low quality of life.